Changes in neuromuscular structure and functions of human colon during ageing are region-dependent. Issue 7 (18th September 2018) - Broad, John; Kung, Victor W S; Palmer, Alexandra; Elahi, Shezan; Karami, Azadeh; Darreh-Shori, Taher; Ahmed, Shafi; Thaha, Mohamed Adhnan; Carroll, Rebecca; Chin-Aleong, Joanne; Martin, Joanne E; Saffrey, M Jill; et al.
Abstract : Objective: To determine if human colonic neuromuscular functions decline with increasing age. Design: Looking for non-specific changes in neuromuscular function, a standard burst of electrical field stimulation (EFS) was used to evoke neuronally mediated (cholinergic/nitrergic) contractions/relaxations in ex vivo muscle strips of human ascending and descending colon, aged 35–91 years (macroscopically normal tissue; 239 patients undergoing cancer resection). Then, to understand mechanisms of change, numbers and phenotype of myenteric neurons (30 306 neurons stained with different markers), densities of intramuscular nerve fibres (51 patients in total) and pathways involved in functional changes were systematically investigated (by immunohistochemistry and use of pharmacological tools) in elderly (≥70 years) and adult (35–60 years) groups. Results: With increasing age, EFS was more likely to evoke muscle relaxation in ascending colon instead of contraction (linear regression: n=109, slope 0.49%±0.21%/year, 95% CI), generally uninfluenced by comorbidity or use of medications. Similar changes were absent in descending colon. In the elderly, overall numbers of myenteric and neuronal nitric oxide synthase-immunoreactive neurons and intramuscular nerve densities were unchanged in ascending and descending colon, compared with adults. In elderly ascending, not descending, colon numbers of cell bodies exhibiting choline acetyltransferase immunoreactivity increased compared with adults (5.0±0.6 vs 2.4±0.3 neurons/mm myenteric plexus, p=0.04). Cholinergically mediated contractions were smaller in elderly ascending colon compared with adults (2.1±0.4 and 4.1±1.1 g-tension/g-tissue during EFS; n=25/14; p=0.04); there were no changes in nitrergic function or in ability of the muscle to contract/relax. Similar changes were absent in descending colon. Conclusion: In ascending not descending colon, ageing impairs cholinergic function.